Effect of six-week pranayama training on the serum levels of cortisol and blood pressure in pregnant women in the third trimester - Marzieh Abedi Amiri; Seyed Mohsen Avandi; Sedigheh Esmaeilzadeh (Mashhad University of Medical Sciences, 2018)
Introduction: The elevation of stress hormones at the end of pregnancy will cause many problems, including a change in blood pressure. The extreme enhancement of gestational hypertension is associated with dangers, such as intrauterine growth restriction, preterm birth, placental abruption, and stillbirth. The aim of this study was to evaluate the effect of six weeks of pranayama training during the third trimester of pregnancy on serum cortisol and blood pressure levels in pregnant women. Methods: This randomized clinical trial was conducted on 18 women in the third trimester of pregnancy referring to a specialized gynecology clinic in Babol, Iran. The subjects were randomly divided into two groups of pranayama (n=8) and control (n=10). The pranayama group performed the relaxation and respiratory exercises for 6 weeks (two 60-minute sessions a week). Fasting blood pressure measurement and blood sampling (using median cubital vein) were performed in resting conditions 48 h before and after the implementation of the intervention. The data were analyzed in SPSS software (version 23) using Shapiro-Wilk test, as well as independent and paired sample t-tests. P-value less than 0.05 was considered significant. Results: The results showed that pranayama training significantly decreased serum cortisol levels (P=0.035). Furthermore, diastolic blood pressure in the pranayama group showed a significant decrease, compared to that in the control group (P=0.001). However, there was no significant difference between pranayama training and control groups in terms of systolic blood pressure (P=0.079). Conclusion: Given the importance of the third trimesters of pregnancy, pranayama exercises can be used to control blood pressure and other stress complications in case of high stress in pregnant women.